The Relationship Between Financial Behavior with its Determinants and Well-Being of College Students in Bandung - Samuel Santo Patarma Raja Panukunan Hasibuan (PT. Publikasiku Academic Solution, 2023)
Financial Literacy has become a strategic national focus in Indonesia and the “youth” group, which includes college students, have become a focus age group for this strategy. However, research have found that the financial behavior exhibited by Indonesian college students is categorized as poor. Research studies have found that financial behavior has an effect to financial well-being, which then would affect the subjective well-being of these students. Thus, this research explored what may cause the financial behaviors of Indonesian college students, and how these behaviors would affect their financial and subjective well-being. A quantitative approach using questionnaire is employed and 305 responses of college students from universities in Bandung City is collected. Then, descriptive statistics and PLS-SEM methodologies are used to analyze each variable and the relationships between them. Among the determinants, only Financial Knowledge is found to affect the Financial Behaviors, and this research does not support the relationship between Financial Behavior to Financial Well-Being. A healthier financial condition is found to increase the frequency of positive feelings over negative feelings in college students. Interestingly, a healthier financial condition is found to negatively influence the life satisfaction of students. This study’s findings contribute to the research body of financial literacy in Indonesia and explore a conceptual model that have not been studied on Indonesian college student. The findings would encourage college students to strive towards getting heathier financially and help policymakers or businesses who are targeting the segment of college students, particularly in Bandung City.